THE DENSITY IMPACT ON THE MATHEMATICAL MODEL OF THE SELF-PROPELLED PARTICLES IN THE HETEROGENEOUS MEDIA - Arshad Ali; Israr Ahmed; Sohail Ahmed; Mashooque Ali Mahar; kashif Ali Dharejo (Spectrum of Engineering Sciences, 2025)
The collective dynamics of the self-driven particles was investigated mathematically and computationally. A two-dimension square shaped heterogeneous medium with boundaries was developed to study the behavior of the self-propelled particles in the existence of the static obstacles. It was examined that how changes in density impact on the collective motion of the SPP’s within the Heterogeneous media. The maximum cohesive motion and ferromagnetic alignment of the particles was determined in the presence of optimal noise . It was observed that as the number of the particles was increased, exceptional collective alignments among the particles were formed. At and an uninterrupted continuous escalation in motion was identified and the value of collective motion of self-propelled particles was reached at out of at time steps. The inherited order parameter among the particles in this model is an important critical factor.